Urgensi Agama dan Spiritualitas - Sumanto Al Qurtuby (Reformed Center for Religion and Society, 2022)
The emergence of “public religion” in various countries, including Indonesia, shows that religion and spirituality have not disappeared from the public sphere. The articles in this edition demonstrated a common thread that religion and spirituality are still seen and believed to be essential entities by (some) people. They can serve as sources of inspiration and positive activities in smaller scopes (such as family and village) and those in the broader community (such as nation and state). Religion and spirituality have also been shown to have meaningful and valuable contributions to their adherents’ social and individual lives. Thus, Nietzsche’s predictions about the “death of God” (read: religion and spiritual systems), for the time being, have not been proven in Indonesia.